1997
DOI: 10.1007/s007050050259
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of the long non-coding M-F genome region of wild-type and vaccine measles viruses

Abstract: The sequence of the 300 nucleotides region of the measles virus genome was determined that includes a part of the 3'-untranslated region of the matrix (M) gene, the intergenic region and a part of the 5'-untranslated region of the fusion (F) gene [M-F region] for vaccine strain Leningrad-16 and 14 wild-type isolates. The data obtained demonstrate the variability of this long non-coding M-F region. No mutations in this region of the genome were found which seem to be specific for vaccine strains of measles viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…The unique features of the region between the M and F proteins of morbilliviruses have raised questions about its function in viral replication and virulence (2,6,7,10,15,25). In this study, we present evidence that the amino-terminal extension (residues 1 to 135) of the CDV F protein is more than a classical signal sequence.…”
Section: Discussionmentioning
confidence: 77%
“…The unique features of the region between the M and F proteins of morbilliviruses have raised questions about its function in viral replication and virulence (2,6,7,10,15,25). In this study, we present evidence that the amino-terminal extension (residues 1 to 135) of the CDV F protein is more than a classical signal sequence.…”
Section: Discussionmentioning
confidence: 77%
“…The isolates Buk 88, Gag 88, and Il 88 [Tikhonova et al, 1992], and the isolates Nov 1/96, 2/96, and 3/96, show that genotype A has circulated in the European as well as in the Asiatic part of Russia during the past 10 years. Phylogenetic analysis using a part of the noncoding M-F genomic region [Heider et al, 1997] also demonstrated that these Russian isolates belonged to genotype A. Observations of other affected groups also indicate that genotype A has been present in Russia and other regions of the world within the past 10 years. The sequence published by Jin et al [1996] for the Loss strain isolated in Russia in 1988 corresponds to genotype A.…”
Section: Resultsmentioning
confidence: 87%
“…Heider et al [36] compared only a part (from 4725 to 5024 nt) of the long noncoding M-F genome region of wild-type (different genotypes) and measles vaccine strains [36]. Results of their analysis have shown a significant difference between the genotypes in this part of measles genome, but a high degree of conservation within each genotype.…”
Section: Resultsmentioning
confidence: 96%